2014
DOI: 10.1186/1471-2458-14-287
|View full text |Cite
|
Sign up to set email alerts
|

Mothers impose physical activity restrictions on their asthmatic children and adolescents: an analytical cross-sectional study

Abstract: BackgroundPhysical activities are important for children and adolescents, especially asthmatics. A significant proportion is considered less active than their non-asthmatic peers and mother’s beliefs about asthma are thought to be a determinant factor.The research objectives were to investigate whether mothers try to impose limitations on the physical activity (PA) of their asthmatic children/adolescents; identify associated factors; and explore if this attitude has any impact on children’s PA levels.MethodsIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…22 Similarly, Brazilian data have shown that 96% of mothers of children aged 9-19 years and young people with asthma reported that they felt that physical activity was important for their child but 37% of the sample restricted their child's physical activity opportunities. 23 The same study also reported that 37% of mothers reported that exercise was dangerous for children with asthma, but there was no evidence of an association between the severity of the child's asthma and his or her physical activity. Qualitative data from Scotland have shown that many parents and school staff were very anxious about children with asthma being physically active, and that physical activity was perceived as a threat to asthma control.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…22 Similarly, Brazilian data have shown that 96% of mothers of children aged 9-19 years and young people with asthma reported that they felt that physical activity was important for their child but 37% of the sample restricted their child's physical activity opportunities. 23 The same study also reported that 37% of mothers reported that exercise was dangerous for children with asthma, but there was no evidence of an association between the severity of the child's asthma and his or her physical activity. Qualitative data from Scotland have shown that many parents and school staff were very anxious about children with asthma being physically active, and that physical activity was perceived as a threat to asthma control.…”
Section: Discussionmentioning
confidence: 94%
“…For example, qualitative research with children aged 8–10 years in New York showed that school management of inhalers and poor asthma control were key factors that affected physical activity participation 22. Similarly, Brazilian data have shown that 96% of mothers of children aged 9–19 years and young people with asthma reported that they felt that physical activity was important for their child but 37% of the sample restricted their child's physical activity opportunities 23. The same study also reported that 37% of mothers reported that exercise was dangerous for children with asthma, but there was no evidence of an association between the severity of the child's asthma and his or her physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…After TR the observed EIB prevalence in the studied population was 56% (19 children), somewhat higher than that found in other studies of Brazilian patients with asthma of the same age (33% to 52%). 17,18 After EVH, 50% (17 with asthma) had a positive challenge result. The agreement between the responses measured by the 2 bronchial challenge methods was 71%, but the Cohen k coefficient used to measure chance-corrected nominal scale agreement was only moderate (k ¼ 0.412).…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, health perception of the parents was found to be associated with the activity level of children with asthma. 17 Parents agreed that exercise was hazardous to asthmatic children and therefore restrained their children from engaging in physical activity. Considering the motivations for a children to be active, perception and convenience for exercise 18 may be as important as objective observation.…”
Section: Discussionmentioning
confidence: 99%